Characterization of kiwifruit volatile compounds using HS-SPME/GC-MS (Research, Society and Development, 2020)
The kiwi fruit (Actinidia deliciosa) has greater commercial importance among the 70 species of the genus Actinidia. When ripe, the kiwi produces a set of volatile compounds that make up the characteristic aroma and sweet taste of the Actinidia deliciosa variety, being highly appreciated by the population. The present study aimed to detect volatile compounds in samples of a commercial kiwi cultivar using solid phase microextraction in headspace mode (HS-SPME) combined with gas chromatography coupled to mass spectrometry (GC/MS). By this method, 10 volatile compounds were found, these of the chemical classes of alcohols, aldehydes, esters, terpenes and ketonas. Esters represented the predominant chemical class, corresponding to 57.10% of the relative composition of the volatile compounds identified. It was concluded that the characterization of volatile compounds of kiwi was effective by the use of HS-SPME/CG-MS, allowing to identify that the predominant chemical class in this fruit is represented by esters.